The Israeli national policy for discontinuation of isolation of carbapenem-resistant Enterobacterales carriers by carbapenemase type: a retrospective cohort study. (October 2021) - Dickstein, Yaakov; Solter, Ester; Schwartz, David; Nutman, Amir; Harevrich, Inga; Wulffhart, Liat; Carmeli, Yehuda; Schwaber, Mitchell J.
Abstract: Objectives: The Israeli national policy for containing carbapenemase-producing Enterobacterales (CPE) includes a protocol allowing for discontinuation of carrier status following spontaneous decolonization. We examined the strategy's effectiveness based on carbapenemase type. Methods: We performed a retrospective cohort study comparing individuals colonized with KPC- or NDM-producing Enterobacterales who underwent the process of isolation discontinuation. The primary outcome was reversion of carrier status, i.e. re-identification of the same CPE species following isolation discontinuation. We used survival analysis to estimate overall hazard ratio and performed competing-risks analysis using a Fine–Gray subdistribution hazard model and cause-specific hazard ratios. Results: Between 1 January 2006 and 1 January 2019 we identified 1694 individuals who met inclusion criteria, including 1337 (78.9%) carriers of KPC-producing Enterobacterales, 305 (18.0%) carriers of NDM-producing Enterobacterales and 52 (3.1%) carriers of dual KPC-/NDM-producing Enterobacterales . A total of 134 individuals (7.9%) had reversion of carrier status: 9.1% (121/1337) and 4.3% (13/305) of individuals with KPC- and NDM-producing Enterobacterales, respectively. The subdistribution hazard ratio of status reversion was not increased among carriers of NDM producers compared with KPC producers (0.567, 95% CI 0.320–1.000], p 0.052). Cause-specific hazard ratios yielded similar results (0.522, 95% CI 0.291–0.937, p 0.029. Conclusions: Carriage of NDM-producing Enterobacterales was not associated with higher rates of reversion to carrier status following spontaneous decolonization than was carriage of KPC-producing Enterobacterales .